The BtaF Adhesin Is Necessary for Full Virulence During Respiratory Infection by Brucella suis and Is a Novel Immunogen for Nasal Vaccination Against Brucella Infection - Muñoz González, Florencia (2019)
Brucella enters their hosts mostly through mucosae from where it spreads systemically.Adhesion to extracellular matrix (ECM) components or to host cells is important for theinfectious process, and is mediated by several adhesins, including the BtaF trimericautotransporter. Although Th1 responses and gamma interferon (IFN-g) are important forprotection, antibodies able to block adhesions might also contribute to prevent Brucellainfection. We evaluated the importance of BtaF for respiratory Brucella infection, andcharacterized the immune response and protection from mucosal challenge induced bynasal vaccination with recombinant BtaF. While lung CFU numbers did not differ at day1 p.i. between mice intratracheally inoculated with B. suis M1330 (wild type) and thosereceiving a 1btaF mutant, they were reduced in the latter group at 7 and 30 days p.i.For vaccination studies the BtaF passenger domain was engineered and expressed asa soluble trimeric protein. Mice were immunized by the nasal route with BtaF or saline(control group) plus the mucosal adjuvant c-di-AMP. Specific anti-BtaF antibodies (IgGand IgA) were increased in serum, including a mixed IgG2a/IgG1 response. In vitro,these antibodies reduced bacterial adhesion to A549 alveolar epithelial cells. Specific IgAantibodies were also increased in several mucosae. Spleen cells from BtaF immunizedmice significantly increased their IL-2, IL-5, IL-17, and IFN-g secretion upon antigenstimulation. In cervical draining lymph nodes, antigen-experienced CD4+ T cells weremaintained mainly as central memory cells. A BtaF-specific delayed-type hypersensitivityresponse was detected in BtaF immunized mice. Lung cells from the latter producedhigh levels of IFN-g upon antigen stimulation. Although nasal immunization with BtaF didnot protect mice against B. suis respiratory challenge, it conferred significant protectionfrom intragastric challenge; the splenic load of B. suis was reduced by 3.28 log CFU inimmunized mice. This study shows that nasal vaccination with BtaF+c-di-AMP protectsagainst intragastric challenge with B. suis by inducing local and systemic antibodyresponses, central memory CD4+ T cells and strong Th1 responses. Therefore, althoughBtaF vaccination did not protect fromB. suis respiratory infection, this adhesin constitutesa promising immunogen against mucosal B. suis infection.